Effect of Work Stress, Work Compensation and Organizational Culture on Employee Performance - Dearyani Eka Dharma; Moehammad Unggul Januarko (Golden Ratio of Data in Summary, 2026)
Employee performance has a dominant influence in the process of achieving company goals. Various efforts to improve employee performance are expected to enable employees to provide their optimal abilities for the benefit of the company. This study aims to analyze the influence of workload, work compensation, and organizational culture on employee performance in order to contribute to a deeper understanding of the factors that influence employee performance in companies. This research is expected to provide practical guidance for companies in developing strategies to improve employee performance so that the company can achieve its desired goals and remain competitive and sustainable in a dynamic business environment. Data collection was carried out by distributing questionnaires to 135 employees. The analysis method used in the study was multiple linear regression using statistical software. The results of the study showed that work stress did not affect employee performance, compensation affected employee performance and organizational culture affected employee performance in a distributor manufacturing company. Furthermore, work stress, work compensation and organizational culture together influence employee performance.